Original paperIgE-mediated 15-hydroxyeicosatetraenoic acid (15-HETE) generation by peripheral blood leukocytes: its association with basophil activation - Michalak, Anna; Lewandowska-Polak, Anna; Moskwa, Sylwia; Kowalski, Marek L.; Grzegorczyk, Janina Ł. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Allergen-induced basophil activation has been associated with the release of several mediators and with an increased expression of CD203c molecules on basophils. Aim : To assess the influence of specific allergens on the generation of 15-hydroxyeicosatetraenoic (15-HETE) from peripheral blood leukocytes in relation to basophil activation, on the basis of CD203c molecule expression and histamine release. Material and methods: The study included 15 patients with clinical symptoms of birch pollen allergy confirmed by a positive skin prick test with the birch allergen, and 6 healthy controls. Leukocytes isolated from peripheral blood were incubated with 3 concentrations of the birch pollen allergen (Bet v 1), anti-IgE or with ionophore A23187. Results : In vitro challenge of leukocytes from allergic patients with 1 ng/ml of allergen induced a significant increase in 15-HETE generation. An increase above 30% was observed in almost half the allergic patients, with mean values ranging from 40% to 46%, but not in healthy controls. Anti-IgE antibodies increased 15-HETE generation in 5 patients (termed IgE+), and the allergen induced a significant increase in 15-HETE in all patients who reacted to anti-IgE. The mean CD203c expression on basophils of the allergic patients increased after allergen challenge, but a significant increase (> 30%) was observed only in patients who demonstrated an increased expression after anti-IgE exposure. A significant correlation was seen between 15-HETE generation and histamine release induced by the highest concentration of the allergen (r = 0.95; p < 0.01). Conclusions : Allergen-induced, IgE-mediated activation of basophils is associated with a significant increase in 15-HETE generation.